Hubungan Pengetahuan Ibu dengan Kelengkapan Imunisasi Dasar Pada Bayi di BPM Bidan "L" Kota Bandung - Maya Indriati; Sheli Riani; Siti Nurmala (Jurnal Sehat Masada, 2024)
Immunization is an effort to increase the body's immunity against disease. Providing immunization is a health effort that has been proven to be effective and has a positive impact on improving the health status of mothers and children in Indonesia. The aim of this research was to determine the relationship between maternal knowledge and the completeness of basic immunization for babies, using a descriptive correlation method with a crosssectional approach. The population in this study were mothers who had babies aged 12-24 months at BPM Midwife L. The sample was selected using a simple random sampling technique with a sample size of 42 people. Data collection used a questionnaire, while analysis used chi square (Î± = 0.05). The results of univariate analysis showed that the majority of mothers had good knowledge (69.1%) and had received complete basic immunization (88.1%). The results of the bivariate analysis obtained a p value of 0.000 <0.05, it can be concluded that there is a relationship between maternal knowledge and the completeness of basic immunization for babies.